Analisis Pengetahuan, Sikap, Perilaku dan Kesadaran Lingkungan Masyarakat terhadap Pengolahan Sampah Berbasis 3R di Desa Kojadoi - Sukardi Sukardi; Jonas K. G. D Gobang; Hartina Iyen; Angelinus Vincentius; Cristofel O. N Pale (Dinasti Research, 2026)
Waste management based on the principles of reduce, reuse, and recycle (3R) requires active community participation, beginning at the source of waste generation. This study aimed to analyze the levels of knowledge, attitudes, behavior, and environmental awareness among residents of Kojadoi Village regarding 3R-based waste management and to identify the main constraints affecting its implementation at the household level. The study employed a descriptive quantitative design. Data were collected from 100 respondents using a questionnaire measured on a five-point Likert scale. The data were analyzed using total scores, mean scores for each dimension, respondent classifications, item-level scores, and patterns identified from open-ended responses. The results showed an overall mean Likert score of 2.60, indicating a moderate level of 3R-based waste management. Among the respondents, 44% were classified in the low category, 46% in the moderate category, and 10% in the high category. Environmental awareness obtained the highest mean score of 2.746, followed by attitudes toward waste management at 2.698, waste management behavior at 2.482, and knowledge at 2.474. The lowest-scoring indicators were recycling behavior, with a mean score of 1.96; household separation of organic and inorganic waste, with a mean score of 2.16; and understanding of the 3R concept, with a mean score of 2.20. These findings indicate that the community has a moderate level of environmental awareness and relatively positive attitudes. However, these conditions have not been adequately supported by technical knowledge, appropriate facilities, and consistent household-level 3R practices. The main constraints include limited availability of separate waste bins, inadequate waste-processing equipment, insufficient technical knowledge, and weak recycling habits. Therefore, practical 3R education, the provision of separate waste bins, basic recycling training, and the establishment of village environmental cadres are recommended to strengthen community participation in sustainable waste management